2019
DOI: 10.1177/000313481908501235
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral Axillary Metastases in Breast Cancer: Stage IV Disease or a Locoregional Event?

Abstract: Contralateral axillary metastasis (CAM) in breast cancer is presently treated as a stage IV disease. We hypothesized that this disease pattern is a manifestation of direct aberrant lymphatic drainage and would behave more similar to advanced locoregional disease. This is a single-site, retrospective review of patients with biopsy-proven CAM from 2008–2017. Descriptive analysis was performed. Twenty-three patients met the inclusion criteria. The median disease-free interval from primary tumor treatment to diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 10 publications
0
14
1
Order By: Relevance
“…In this cohort, the estimated overall survival was 72% at 5 years (95% CI 54–83), and the estimated disease-free survival was 61% at 5 years (95% CI 44–74); the prognosis of CAM in these case series is not comparable to the prognosis of metastatic breast cancer. In contrast, Guru et al [13] suggested that the natural history of CAM is similar to that of stage IV disease, with a relatively poor prognosis; however, this study also suggests that patients with CAM identified via SLNB have improved outcomes compared with those with clinical presentation of CAM. This situation might be comparable to that of our patient, thus neither echography nor CT identified the CAM.…”
Section: Discussioncontrasting
confidence: 73%
“…In this cohort, the estimated overall survival was 72% at 5 years (95% CI 54–83), and the estimated disease-free survival was 61% at 5 years (95% CI 44–74); the prognosis of CAM in these case series is not comparable to the prognosis of metastatic breast cancer. In contrast, Guru et al [13] suggested that the natural history of CAM is similar to that of stage IV disease, with a relatively poor prognosis; however, this study also suggests that patients with CAM identified via SLNB have improved outcomes compared with those with clinical presentation of CAM. This situation might be comparable to that of our patient, thus neither echography nor CT identified the CAM.…”
Section: Discussioncontrasting
confidence: 73%
“…CAM is the most studied DLM. From 1995-2020, three relatively larger sample-sized studies reported on a total of 154 patients with CAM [8,17]. In one of these studies, 47 patients with CAM were suspected of having N3 disease, showing better response than at other sites of distant dissemination, when subjected to surgical and systemic treatments with curative intent [8]; while the other two studies draw a contrary conclusion from 28 and 23 patients, respectively that CAM was most likely to be stage IV.…”
Section: Discussionmentioning
confidence: 99%
“…In one of these studies, 47 patients with CAM were suspected of having N3 disease, showing better response than at other sites of distant dissemination, when subjected to surgical and systemic treatments with curative intent [8]; while the other two studies draw a contrary conclusion from 28 and 23 patients, respectively that CAM was most likely to be stage IV. [10,17] KROG 18 − 02 study that included 78 patients indicated that patients with breast cancer who had ipsilateral CLM without other distant metastasis might bene t from locoregional treatment of the ipsilateral breast and systemic therapies, just as those with N3c disease. [9] It remains unclear whether DLM should be considered an advanced locoregional stage or distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contralateral axillary metastasis (CAM) is an uncommon event in breast cancer, defined as the identification of tumor deposits in the nodes of the contralateral axilla. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] This may occur as: (1) a synchronous event with an initial locally advanced breast cancer (LABC), (2) a metachronous event in isolation, (3) a synchronous event with an inbreast tumor recurrence and presumed aberrant lymphatic drainage, and lastly as (4) a metachronous event with a local recurrence. Contemporary studies report frequencies ranging from 0.8 to 6%, seen more commonly with recurrent disease than primary diagnoses.…”
mentioning
confidence: 99%